Posture control and complex arm coordination: Analysis of multijoint coordinative movements and stability of stance - Forner-Cordero, A.; Levin, O.; Li, Y.; Swinnen, S. P. (Journal of Motor Behavior, 2007)
The authors addressed the interactions between control of bimanual multijoint coordination tasks and posture. Participants (N = 6) performed 8 coordination patterns that differed in degree of complexity by using their bilateral elbows and wrists under 3 scaled motion speeds while standing on 2 force plates. Results indicated that producing complex bimanual multijoint coordinative tasks affected postural sway, thus resulting in an increase of sway activity. Behavioral as well as mechanical factors accounted for the increased disturbance in postural sway. Those findings suggest that performing complex coordination tasks disrupts postural control in normal young adults.